Inovasi Teknologi Informasi Sebagai Penggerak Pertumbuhan Bisnis Syariah - Salim, Agus; Wahyudi, Dedi (Yayasan Pendidikan Riset dan Pengembangan Intelektual (YRPI), 2024)
This study explores the role of information technology innovation as a driver of growth in Islamic business. Through a comprehensive literature review, the study aims to identify the impacts, challenges, and opportunities arising from the integration of information technology within the Islamic business ecosystem. The methodology employed is a qualitative approach with thematic content analysis of current literature sources. The findings indicate that information technology innovations, including blockchain, artificial intelligence (AI), fintech, big data analytics, cloud computing, and the Internet of Things (IoT), have a significant influence on the growth and transformation of Islamic business. These technologies enhance operational efficiency, transaction transparency, and the accessibility of Islamic financial services. However, their implementation also presents challenges related to Sharia compliance, regulation, and ethical considerations. In conclusion, information technology innovation plays a crucial role as a catalyst for Islamic business growth, opening new opportunities for expansion and service improvement. The recommendations include developing adaptive regulatory frameworks, investing in human resource development, global collaboration for the standardization of best practices, enhancing digital and Islamic financial literacy, and further research on socio-economic impacts. The implementation of these recommendations is expected to maximize the potential of information technology innovation in driving sustainable growth of Islamic business in the digital age.